High resolution single-component resists based on terpolymers having photoacid-generating camphorsulfonyloxymaleimide units - Kim, S.-T.; Kim, J.-B.; Kim, J.-M.; Chung, C.-M.; Ahn, K.-D. (Tokai University, 1997)
[No abstract available]